2017
DOI: 10.1002/chem.201702766
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Characterization of Two Chimeric Sesterterpene Synthases from Penicillium

Abstract: The products of two bifunctional fungal sesterterpene synthases (StTPS), with prenyl transferase (PT) and terpene synthase (TPS) domains from Penicillium, were structurally characterized and their mechanisms studied in detail by labeling experiments. A phylogenetic analysis of the TPS domains of the new and previously characterized enzymes revealed six distinct clades. Enzymes from the same clade catalyze a common initial cyclization step, which suggests the potential for structural predictions from amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0
32

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 58 publications
0
72
0
32
Order By: Relevance
“…Previously characterised enzymes are shown in green, the enzyme characterised in this study is shown in red. AcOS: Aspergillus clavatus ophiobolin F synthase, CgDS: Colletotrichum gloeosporioides dolasta‐1(15),8‐diene synthase, EvAS: E. variecolor astellifadiene synthase, EvQS: E. variecolor quiannulatene synthase, EvSS: E. variecolor stellata‐2,6,19‐triene synthase, EvVS: E. variecolor variediene synthase, FgMS: F. graminearum mangicdiene synthase, NfSS: Neosartorya fischeri sesterfisherol synthase, PaFS: P. amygdali fusicocca‐2,10(14)‐diene synthase, PaPS: P. amygdali phomopsene synthase, PbSS: Penicillium brasilianum sesterbrasiliatriene synthase, PcCS: P. chrysogenum cyclopiane‐type diterpene synthase, PvPS: Penicillium verruculosum preasperterpenoid A synthase …”
Section: Methodsmentioning
confidence: 99%
“…Previously characterised enzymes are shown in green, the enzyme characterised in this study is shown in red. AcOS: Aspergillus clavatus ophiobolin F synthase, CgDS: Colletotrichum gloeosporioides dolasta‐1(15),8‐diene synthase, EvAS: E. variecolor astellifadiene synthase, EvQS: E. variecolor quiannulatene synthase, EvSS: E. variecolor stellata‐2,6,19‐triene synthase, EvVS: E. variecolor variediene synthase, FgMS: F. graminearum mangicdiene synthase, NfSS: Neosartorya fischeri sesterfisherol synthase, PaFS: P. amygdali fusicocca‐2,10(14)‐diene synthase, PaPS: P. amygdali phomopsene synthase, PbSS: Penicillium brasilianum sesterbrasiliatriene synthase, PcCS: P. chrysogenum cyclopiane‐type diterpene synthase, PvPS: Penicillium verruculosum preasperterpenoid A synthase …”
Section: Methodsmentioning
confidence: 99%
“…During the biosynthesis of 18-22 as imilar1 ,3-hydride shift as from cation A to B can be assumed. To investigate this hydride migration, (1,1-2 H 2 )-8a and (1,1-2 H 2 )-8b were synthesised (Scheme S2A, Supporting Information) and enzymatically converted with (7-13 C)GPP [19] by FPPS and TmS. 13 C-NMR analysis of the obtained products established the proposed hydride migrations by slightly upfield shiftedt ripletsf or C11, indicating ad irect 13 C-2 Hb ond ( Figures S96 and S97).…”
mentioning
confidence: 99%
“…Whereas a triplet was observed for C4 in case of the Z sample, a singlet appeared in the E case (Figure B, C), demonstrating a selective movement of H E . Its destination was targeted using (7‐ 13 C)GPP and ( Z )‐ or ( E )‐(4‐ 2 H)IPP with FPPS and TaS resulting in a complementary outcome (Figure D, E). In conclusion, these results clearly show a 1,5‐hydride shift occurring in the cyclization toward 1 (path A).…”
Section: Figurementioning
confidence: 55%